The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5539/mas.v11n12p48
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Organisational Commitment Among Generation -Y in the Malaysian SMEs

Abstract: It is evident from research that Generation-Y constitutes a large proportion in the work force across the globe and hence it is a great challenge to organisations to attract and retain their Gen-Y employees. Various studies have highlighted that the knowledge of organisational commitment is crucial to organisations in developing their longterm performance and growth. This study aims to explore the determinants of organisational commitment among the Generation-Y who are employed in Malaysian SMEs (Johor Bahru, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Likewise, Chen (2019) also indicated that Millennial in Malaysia are currently dominating a large number of working movements as they comprises 50 per cent of the workforce in 2020 and expected to increase to 75 per cent by the year 2025. On the other hand, the study by Ganesan et al (2017) have found out that pay and benefits, training, leadership style, organisational culture and job satisfaction had significant relationship with organisational commitment among Gen Y SMEs employees in Malaysia. Additionally, the chances that employees will remain committed to the organisation rely mainly on their level of productivity and the organisation's commitment to support them (Lee & Chen, 2013;Osa & Amos, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Likewise, Chen (2019) also indicated that Millennial in Malaysia are currently dominating a large number of working movements as they comprises 50 per cent of the workforce in 2020 and expected to increase to 75 per cent by the year 2025. On the other hand, the study by Ganesan et al (2017) have found out that pay and benefits, training, leadership style, organisational culture and job satisfaction had significant relationship with organisational commitment among Gen Y SMEs employees in Malaysia. Additionally, the chances that employees will remain committed to the organisation rely mainly on their level of productivity and the organisation's commitment to support them (Lee & Chen, 2013;Osa & Amos, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…In exchange, the rewards are found to instil a perception of support by the organisation in the minds of the employees, enhancing their commitment (Heathfield 2016). Furthermore, fairness in recognition and distribution of rewards signals out the organisation's concern over its employees increases the commitment of employees with the organisation (Ganesan, Mun & Raman 2017;Huynh 2015). Similarly, Bustamam, Teng and Abdullah (2014) posited that an employee who is satisfied with the rewards provided by an employer voluntarily reciprocates and continually shows a high level of commitment.…”
Section: Organisational Rewards and Organisational Commitmentmentioning
confidence: 99%